The regime of the application judge of penalties in the Algerian legislation - SAFI, Nesrine; TACHOUR, Abdelhafid (Journal of Human Sciences, 2020)
The Algerian legislator adopted a modern approach which supports the necessity of the contribution of the magistracy to the application of the the penalties, He therefore adopted the regime of the enforcement judge of penalties according to the law 05/04 carrying code of penitentiary organization and social reintegration of prisoners, by giving him an important role in controlling the legality of the application of the penalties , in addition to a set of provisions and powers to enable him to carry out the process of reforming and rehabilitating prisoners ,this has been advocated by international conferences and human rights, which are considered to be one of the most important objectives of modern prison policy.